1996
DOI: 10.1002/jbmr.5650110917
|View full text |Cite
|
Sign up to set email alerts
|

Dietary (n-3) and (n-6) polyunsaturates and acetylsalicylic acid alter ex vivo PGE2 biosynthesis, tissue IGF-I levels, and bone morphometry in chicks

Abstract: This study examined the effects of dietary (n-6) and (n-3) polyunsaturated fatty acids (PUFA) and acetylsalicylic acid (ASA) on bone ash content, morphometry, fatty acid composition, ex vivo PGE2 biosynthesis, tissue IGF-I concentration, and serum alkaline phosphatase (ALPase) activity in chicks. Newly hatched chicks were fed a semipurified diet containing soybean oil (S) or menhaden oil / safflower oil (M) at 90 g/kg. At 4 days of age, chicks were divided into four equal treatment groups receiving 0 mg [symbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 46 publications
4
38
0
3
Order By: Relevance
“…Watkins et al [59] have shown that feeding chicks menhaden oil (high in n-3 PUFAs) resulted in a higher serum ALP activity and an increase in the bone formation rate compared to that in chicks given soy-bean oil (high in n-6…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Watkins et al [59] have shown that feeding chicks menhaden oil (high in n-3 PUFAs) resulted in a higher serum ALP activity and an increase in the bone formation rate compared to that in chicks given soy-bean oil (high in n-6…”
Section: Figurementioning
confidence: 99%
“…The effect of PUFAs might be exerted via modulation and reduction of PGE 2 synthesis, reducing inflammation and affecting ALP activity [2,59].…”
Section: Figurementioning
confidence: 99%
“…The high concentration of ALP indicated better reabsorption of bone and moreover 1.2 w-6/w-3 ratio diets showed higher rate of bone formation. In another study [23], an increased production of PGE2 in tibia of chicks given a semipurified diet containing soya bean oil, high in w-6 fat was associated with a lower rate of bone formation compared with that of chicks fed a low dietary ratio of w-6/w-3 fatty acids. In a further study [24], rats fed with a lower dietary ratio of w-6/w-3 fat showed increased bone marrow cellularity and bone strength.…”
Section: Osteoporosis and Cardiovascular Diseasementioning
confidence: 89%
“…Further support for the role of polyunsaturated fatty acids in the pathogenesis of osteoporosis and hip fracture may be provided from the experimental studies [22][23][24][25]. In a experimental study [22], 15 rats were fed identical diets except that w-6/w-3 ratio differed.…”
Section: Osteoporosis and Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation